1995
DOI: 10.1111/j.1476-5381.1995.tb15109.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the desglycinyl metabolite of remacemide hydrochloride (FPL 12495AA) and dizocilpine (MK‐801) on endogenous amino acid release from mouse cortex

Abstract: 1 In this study the effect of FPL 12495AA, the desglycinyl metabolite of remacemide hydrochloride and dizocilpine (MK-801), on potassium-and veratridine-stimulated release of neurotransmitter amino acids from mouse cortical slices was investigated.2 Veratridine (20 gM) and potassium (60 mM) produced a preferential release of glutamate and aspartate. Potassium-stimulated release was calcium-dependent, while veratridine-stimulated release was only partially affected by removal of calcium from the medium. 3 FPL 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In addition, this study showed that losigamone reduced veratridine-induced release of glutamate at concentrations of 100 mM and above, and potassium-induced release of glutamate and potassium-and veratridine-induced release of aspartate at concentrations of 200 mM. As previously shown, potassium-stimulated release is calcium-dependent while veratridine-stimulated release is only partially a ected by removal of calcium from the medium (Srinivasan et al, 1995).…”
Section: Min Losigamonesupporting
confidence: 54%
See 3 more Smart Citations
“…In addition, this study showed that losigamone reduced veratridine-induced release of glutamate at concentrations of 100 mM and above, and potassium-induced release of glutamate and potassium-and veratridine-induced release of aspartate at concentrations of 200 mM. As previously shown, potassium-stimulated release is calcium-dependent while veratridine-stimulated release is only partially a ected by removal of calcium from the medium (Srinivasan et al, 1995).…”
Section: Min Losigamonesupporting
confidence: 54%
“…However, the e ect of losigamone in reducing potassium-stimulated release of glutamate and aspartate, is not a sodium channel e ect as TTX does not reduce release. The action of losigamone probably involves NMDA receptor antagonism as we have previously shown that dizocilpine (MK-801) reduced potassium-stimulated release of glutamate (Srinivasan et al, 1995).…”
Section: Min Losigamonementioning
confidence: 99%
See 2 more Smart Citations
“…The cerebral cortex contains a large number of glutamatergic neurons and the dendrites in these neurons also possess NMDA receptors (32). If activation of these receptors is blocked, as is probably the case by NMDA antagonist, then augmentation of glutamate release by NMDAreceptor facilitation will not occur (33). Thus, PCP prevents both inhibitory GABAergic and excitatory glutamatergic regulations directly in pFC.…”
Section: Discussionmentioning
confidence: 99%